Compound sophorae decoction enhances intestinal barrier function of dextran sodium sulfate induced colitis via regulating notch signaling pathway in mice - Wu, Hui; Chen, Qian-Yun; Wang, Wen-Zhu; Chu, Si; Liu, Xing-Xing; Liu, Yu-Jin; Tan, Chen; Zhu, Feng; Deng, Shuang-Jiao; Dong, Ya-Lan; Yu, Ting; Gao, Fei; et al. (Biomedicine & pharmacotherapy, 2021)
•Compound sophorae decoction can alleviate the clinical manifestations and pathological damage of UC.•Compound sophorae decoction abates intestinal inflammation and restores colonic barrier function.•Compound sophorae decoction can regulate Notch signaling pathway in DSS-induced colitis mice. Compound sophorae decoction (CSD), a Chinese Herbal decoction, is frequently clinically prescribed for patients suffered from ulcerative colitis (UC) characterized by bloody diarrhea. Yet, the underlying mechanism about how this formulae works is remain elusive. In the present study, the experimental colitis in C57BL/6 J mice was induced by oral administration of standard diets containing 3% dextran sodium sulfate (DSS), and CSD was given orally for treatment at the same time. The clinical symptoms including stool and body weight were recorded each day, and colon length and its histopathological changes were observed. Apoptosis of colonic epithelium was studied by detecting protein expression of cleaved caspase-3, and cell proliferation by Ki-67 immunohistochemistry. Tight junction complex like ZO-1 and occludin were also determined by transmission electron microscope and immunofluorescence. The concentration of FITC-dextran 4000 was measured to evaluate intestinal barrier permeability and possible signaling pathway was investigated. Mucin2 (MUC2) and notch pathway were tested through western blot. The M1/M2 ratio in spleen and mesenteric lymph nodes were detected by flow cytometry. And the mRNA levels of iNOS and Arg1 were examined by qRT-PCR. CSD could significantly alleviate the clinical manifestations and pathological damage. Body weight loss and DAI score of mice with colitis were improved and shortening of colon was inhibited. The administration of CSD was able to reduce apoptotic epithelial cells and facilitate epithelial cell regeneration. Increased intestinal permeability was reduced in DSS-induced colitis mice. In addition, CSD treatment obviously up-regulated the expression of ZO-1 and occludin and the secretion of MUC2, regulated notch signaling, and decreased the ratio of M1/M2. These data together suggest that CSD can effectively mitigate intestinal inflammation, promote phenotypic change in macrophage phenotype and enhance colonic mucosal barrier function by, at least in part, regulating notch signaling in mice affected by DSS-induced colitis.